Response of jiggs grass to inoculation with plant growth-promoting microrganisms - Cruz, Sonia Purin da; Basso, Kelen Cristina (Scientia Agraria Paranaensis, 2021)
Brazil is the second world producer of bovine meat, which often relies on preserved forage to decrease seasonality of forage production. Increased forage accumulation may be favored by technologies such as inoculation. Research works on this theme have been conducted with Azospirillum brasilense associated to oats, ryegrass and guinea grass. However, response of jiggs, a widely cultivated perennial grass, to plant growth-promoting microrganisms is poorly understood. Hence this study aimed to assess effects of inoculation on development of Cynodon dactylon cv. Jiggs. Four treatments were tested: T1) control, T2) Inoculation with A. brasilense, T3) Inoculation with Azospirillum, Rhizobium, Pseudomonas and Saccharomyces, T4) Inoculation + Reinoculation with Azospirillum, Rhizobium, Pseudomonas and Saccharomyces. Forage mass, percentage of leaves, stems, dead mass, reproductive structures and leaf/stem ratio were measured. Data were submitted to analysis of variance, and when significant effects were detected, means were separated by LSD Test. Positive effects of inoculation were recorded at all evaluations, mostly concerning percentage of leaves and leaf/stem ratio. A. brasilense improved leaf/stem ratio up to 56%. Also, a 64% increment on this parameter was obtained with Azospirillum, Rhizobium, Pseudomonas and Saccharomyces. Modifications of plant morphology components are important since grasses with more percentage of leaves increase nutritional value of haylage. Morphology of Cynodon dactylon cv. Jiggs is affected by Azospirillum, Rhizobium, Saccharomyces and Pseudomonas, improving aspects related to palatability and preferred grazing of livestock animals.